Improvement of methodology for assessing technological properties of grain and forecasting bakery product quality - P. V. Medvedev; V. A. Fedotov (Новые технологии, 2019)
Currently, there is a trend of deterioration in technological properties of wheat grain, which entails natural decrease in the quality of bakery products. As a result, the widespread use of ready-made mixes and quality improvers in the baking industry has become traditional. Achieving the required high quality of bakery products is possible due to the flexible management of technological production modes, which, in turn, is possible only with the most reliable assessment of baking advantages of grain raw materials.Therefore, an important task of the baking industry is to minimize the analyzed factors of quality formation in order to increase the prognostic ability of consumer properties of bakery products. The solution can be achieved by developing production solutions due to the establishment of certain technological production parameters based on information about the quality of wheat flour used.The purpose of the research is to study the influence of the physical and chemical parameters of wheat grain on the formation of the quality of bakery products and, based on the patterns found, development of methodological approaches to quality management of bakery products.Laboratory grain milling of the most popular wheat varieties of the Orenburg region has been carried out at Nagema mill; the flour produced corresponds to the first grade. Bread has been made by a sponge dough method according to the white bread recipe. Sponge dough humidity indicator has been used as a controlling technological production parameter during bread making process. Sponge dough humidity has been 41 % to 72 % with a step of 1 %. Grain quality has been determined by grain hardness, that is, a physical and chemical indicator determining the baking quality of flour.It has been established that quality control of bakery products is possible due to the choice of dough humidity, taking into account the hardness of grain, which serves as raw material for the production of flour.